Zn2+-dependent surface behavior of diacylglycerol pyrophosphate and its mixtures with phosphatidic acid at different pHs - Villasuso, Ana Laura (2014)
Diacylglycerol pyrophosphate (DGPP) is a minor lipid that attenuates the phosphatidic acid (PA) signal, and also DGPP itself would be a signaling lipid. DGPP is an anionic phospholipid with a pyrophosphate group attached to diacylglycerol that was shown to respond to changes of pH, thus affecting the surface organization of DGPP and their interaction with PA. In this work, we have investigated how the presence of Zn2+, modulates the surface organization of DGPP and its interaction with PA at acid and basic pHs. Both lipids formed expanded monolayers at pH 5 and 8. At pH 5, monolayers formed by DGPP became stiffer when Zn2+was added to the subphase,  while the surface potential decreased. At this pH, Zn2+ induced a phase transition from an expanded to a condensed phase state in monolayers formed by PA. Conversely, at pH 8 the effects induced by the presence of Zn2+ on the surface behaviors of the pure lipids were smaller. Thus, the interaction of the bivalent cation with both lipids was modulated by pH and by the ionization state of the polar head-groups. Mixed monolayers of PA and DGPP showed a non-ideal behavior and were not affected by the presence of Zn2+ at pH 8. This could be explained considering that when mixed, the lipids formed a close packed monolayer that could not be further modified by the cation. Our results indicate that DGPP and PA exhibit expanded and condensed phase states depending on pH, on the proportion of each lipid in the film and on the presence of Zn2+. This may have implications for a possible role of DGPP as a signaling lipid molecule.